Moving from Critical to Constructive Thinking - Shaw, Perry W. H. (Evangelical review of theology, 2021)
The author, based on his 30 years of experience in cross-cultural education and on biblical interpretation, warns that an over-emphasis on critical thinking can foster sub-Christian understandings of such concepts as autonomy and tolerance. He proposes an approach more typical of collectivist societies, in which students balance their development of a critical voice with respect for accumulated community wisdom.